Comparative Study Of The Word Istawa At Fifth Verse Of Surah Taha In Book Of Tafsir Mafatih Al-Ghaib And Book Of Tafsir Syaikh Al-Islam - Muhammad Alfia Ilfa; Waffada Arief Najiyya (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2023)
The Qur'an is a multi-interpreted holy book, even one word in it can be interpreted with many interpretations that have different trends. This is due to the depth of meaning contained in each word in the Qur'an. Among the words in the Qur'an that are debated among Muslim scholars is the word istawa, the word is seen differently by two paradigm currents that oppose each other, namely the current paradigm of taslim, one of which is led by Imam Ibn Taymiyyah, and the current paradigm of ta'wil, one of which is led by Imam Ar Razi. These two currents further confirm that the Qur'an is universal and multi-interpretive, and add to the treasures of Islamic science, especially in the branch of Qur'anic interpretation and Islamic creed.